Hybrid fuzzy multi-criteria decision making to solve the irrigation water allocation problem in the Tunisian case. (November 2019) - Elleuch, Mohamed Ali; Anane, Makram; Euchi, Jalel; Frikha, Ahmed
Abstract: Modernization and optimization of irrigated agriculture management can involve substantial conflicting factors using the opinions of experts. A combined approach based on concepts of Fuzzy Multi-Criteria Decision-Making (FMCDM) methods and Mathematical Optimization Programming (MOP) model for water allocation problem has been developed. In the first phase, we calculate the criteria weights using fuzzy AHP with water expert opinions. Then, we determine the performance of various water resources performed through the application of the fuzzy TOPSIS method. In the second phase, we solve the water resource allocation using the MOP model with the Multi-Criteria Decision-Making (MCDM) results. The allocation of irrigation water resources using the proposed approach was tested on Sfax irrigation district, southern Tunisia. The achieved results indicate that the combination of the fuzzy MCDM model and the MOP methods provide effective linkages between irrigation expert opinions, economic return, and performance of water resource objectives. Graphical abstract: Unlabelled Image Highlights: Optimization of irrigated agriculture management can involve substantial conflicting factors using opinions of experts. A water allocation problem is developed in this paper. The proposed approach is tested on Sfax irrigation district, southern Tunisia. Our solution provide a linkage between irrigation expert opinions, economic return and performance of water resources.